Experimental Study on Fuel-Switching of Dual-Fuel Gas Turbine Combustor - Feng, Lin; Qiang, Yang; Xiao, Liu; Ming-jia, LI; Jun-hui, Ran; Ya-jun, Li (Frontiers in Energy Research, 2022)
To research the fuel-switching rules for gas turbine dual-fuel combustor, the effects of fuel change rate, fuel compensation rate, permissible fluctuation limit of outlet temperature, and fuel matching on the fuel-switching performance were studied experimentally by using a real dual-fuel gas turbine combustor. The experimental results show that: Increasing fuel change rate can reduce fuel-switching time, but the influence of fuel viscosity and evaporative atomization combustion hysteresis leads to the increase of outlet temperature amplitude fluctuation. The fuel compensation rate corresponds to the optimal solution for this combustion chamber；when the fuel change rate decreases, the optimal fuel compensation coefficient will be increase. Meanwhile, By increasing the allowable fluctuation range of outlet temperature and reducing the difference of calorific value of Natural gas and diesel, the fuel-switching time can be effectively reduced, and the fuel-switching stability can be improved.